2017
DOI: 10.1556/1886.2017.00029
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of infection with Neospora caninum, Leptospira, and bovine herpesvirus type 1 in water buffaloes (Bubalus bubalis) in Veracruz, Mexico

Abstract: We aimed to determine the seroprevalence of infection with Neospora caninum, Leptospira, and bovine herpesvirus type 1 and risk factors associated with these infections in water buffaloes in Veracruz State, Mexico. Through a cross-sectional study, 144 water buffaloes (Bubalus bubalis) raised in 5 ranches of Veracruz were examined for anti-N. caninum and anti-bovine herpesvirus type 1 antibodies by enzyme immunoassays, and anti-Leptospira interrogans antibodies by microscopic agglutination test.Of the 144 buffa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
8
1
2
Order By: Relevance
“…The seroprevalence of N. caninum in water buffaloes can greatly change either between countries or when the protozoan is cause of mono-infection rather than co-infection. Indeed, it can vary from the 24.3% reported in Mexico up to 66.7% described in Israel [15,16] and a recent investigation in northern Brazil showed a N. caninum seroprevalence of 44.0% but 14.8% of the infected animals were co-infected with T. gondii [17]. Studies performed in Italy showed a seroprevalence of N. caninum in water buffaloes ranging between 34.6% and 59% [18,19].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The seroprevalence of N. caninum in water buffaloes can greatly change either between countries or when the protozoan is cause of mono-infection rather than co-infection. Indeed, it can vary from the 24.3% reported in Mexico up to 66.7% described in Israel [15,16] and a recent investigation in northern Brazil showed a N. caninum seroprevalence of 44.0% but 14.8% of the infected animals were co-infected with T. gondii [17]. Studies performed in Italy showed a seroprevalence of N. caninum in water buffaloes ranging between 34.6% and 59% [18,19].…”
Section: Introductionmentioning
confidence: 95%
“…The first of the three aborting pathogens, N. caninum can infect dogs and other canids as definitive hosts and is considered one of the most common causes of abortion in livestock as cattle, sheep, goats, water buffaloes and camels [14,15]. The seroprevalence of N. caninum in water buffaloes can greatly change either between countries or when the protozoan is cause of mono-infection rather than co-infection.…”
Section: Introductionmentioning
confidence: 99%
“…buffalo herd is in Northeast, with 10,437 thousand heads located in the state of Pernambuco (IBGE, 2016). Many serological surveys on N. caninum infection in water buffaloes have been carried out by researchers in different parts of the world with prevalences ranging from 1.50 to 88.30% (BRASIL et al, 2015;CAMPERO et al, 2007;CHRYSSAFIDIS et al, 2015;DUBEY et al, 1998;FUJII et al, 2001;FERROGLIO et al, 2003;GALVÃO et al, 2013;GONDIM et al, 2007;GUARINO et al, 2000;GENNARI et al, 2005;HUONG et al, 1998;HAMIDINEJAT et al, 2015;KONNAI et al, 2008;KONRAD et al, 2013;MEENAKSHI et al, 2007;MOORE et al, 2014;NASIR et al, 2011;NEVERAUSKAS et al, 2015;PORTELLA et al, 2016;RODRIGUES et al, 2005;ROMERO-SALAS et al, 2017;SOUZA et al, 2001;SENGUPTA et al, 2012;SILVA et al, 2010SILVA et al, , 2014SILVA et al, , 2017VOGEL et al, 2006;YU et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…En México, hasta el momento solo hay una prevalencia sérica descrita en búfalos del 24.3% en el estado de Veracruz (14). Con respecto a bovinos, la seroprevalencia encontrada en ambas UPP está por encima de lo reportado en México ya que son pocos los estudios realizados en condiciones similares; entre ellos, se reporta en el estado de Veracruz un 26% de prevalencia general incluyendo ganado lechero, de carne y sus cruzas (15) y de 20.8% en ganado de doble propósito (16).…”
Section: Discussionunclassified